New species of Diamesa (Diptera: Chironomidae) from Tibet: conspecific males and females associated with mitochondrial DNA - Willassen, Endre (Zootaxa, 2005)
Undescribed females representing four morphological types were found in a collection of adult Diamesa from about 5000 m altitude in Rongbuk, Tibet. Short DNA sequences of cytochrome oxidase subunit 2 were used to associate two single males in the material with conspecific females. Diamesa solhoyi n.sp. and Diamesa aculeata n.sp. are described. The complete type material and additional specimens have been deposited in the Insect Collection at the Institute of Zoology, Academia Sinica, Beijing (IZAS). The sequences are deposited in Genbank with accession numbers AM051227–AM051233.